2008
DOI: 10.1089/tmj.2007.0131
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Home Telehealth Following Hospitalization for Heart Failure: A Randomized Trial

Abstract: Previous studies have found that home-based intervention programs reduce readmission rates for patients with heart failure. Only one previous trial has compared telephone and videophone to traditional care to deliver a home-based heart failure intervention program. The objective of this study was to evaluate the efficacy of a telehealth-facilitated postdischarge support program in reducing resource use in patients with heart failure. Patients at a Midwestern Department of Veterans Affairs Medical Center were r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
165
1
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 111 publications
(169 citation statements)
references
References 22 publications
1
165
1
1
Order By: Relevance
“…Some organizations have incorporated the use of equipment such as phone calls and video phones as ways to follow up with patients after discharge. Research indicates no significant difference in the effectiveness of either method in preventing readmissions [6,7] . Hospitals will need to give some consideration to the complexity of new equipment.…”
mentioning
confidence: 97%
“…Some organizations have incorporated the use of equipment such as phone calls and video phones as ways to follow up with patients after discharge. Research indicates no significant difference in the effectiveness of either method in preventing readmissions [6,7] . Hospitals will need to give some consideration to the complexity of new equipment.…”
mentioning
confidence: 97%
“…Previous studies of veterans with chronic conditions who used CCHT have shown lower mortality 24 and healthcare utilization [25][26][27] , as well as improved quality of life 26 and more timely receipt of care 28 . Other work has found increased time to readmission among veterans with heart failure 29 , including a dose-response relationship 30,31 .…”
Section: Va's Care Coordination Home Telehealth (Ccht) Programmentioning
confidence: 92%
“…McInnes and colleagues 62 reported that approximately 29% of veterans used the Internet to search for health information and that higher education, urban residence, and poorer self-reported health status were positively associated with health-related Internet use. Many existing telehealth technologies still require a telephone land line for data transmission, but even when land lines are available, telecommunications infrastructure, particularly in rural areas, can be unreliable 29 . Reliance on cellular and smart phones to the exclusion of land lines by some veterans may yield further disparities in CCHT use.…”
Section: Examine How Disparities May Encumber Use Of Ccht and Mhv Andmentioning
confidence: 99%
“…Further, we identified a number of welldesigned studies that examined access interventions, but they were not included in our review because they did not include data regarding either actual or perceived access outcomes. [29][30][31][32][33][34][35][36][37][38][39][40] Therefore, there are studies that report on the impact of access interventions on downstream outcomes that are not included in this review. As discussed above, we suggest that future research examining access interventions collect and compare a broad range of perceived and actual access outcomes across groups.…”
Section: 16mentioning
confidence: 99%